(untitled) (Research, Society and Development, 2024)
Objective: to evaluate the epidemiological profile, pattern of sun exposure, protective measures and lesion characteristics of patients with actinic keratosis and field cancerization in the city of Lagarto/SE. Methodology: this is a descriptive, cross-sectional and quantitative study using questionnaires over a period of 12 months. Results: the sample included 127 participants, the majority was female, with light skin phototype, low education, average age of 60 years and occupations more exposed to the sun. Participants tended to expose themselves to the sun during the period with the highest incidence of ultraviolet rays, the majority used mechanical photoprotection measures, but only about half of them used sunscreen. Of the total, 124 participants reported having skin lesions, most for more than 1 year, with associated symptoms and in areas of the body most exposed to the sun. Conclusion: most participants belong to risk groups for actinic keratosis and/or skin cancer, work in occupations exposed to the sun, in addition to being exposed at the most critical times of the day. The use of mechanical photoprotection barriers was superior to the use of sunscreen. The characteristics of the interviewees’ skin lesions may indicate a delay in reaching the specialized service, making it important to adjust the local flow to optimize care for this population and ensure their early referral.